Sleep-associated aspects of myofascial pain in the orofacial area among Temporomandibular Disorder patients and controls - Schmitter, Marc; Kares-Vrincianu, Alexandra; Kares, Horst; Lorenzo Bermejo, Justo; Schindler, Hans J. (Sleep medicine, 2015)
Study objectives: To assess sleep-associated aspects of temporomandibular disorder (TMD) with myofascial pain (MP) in the orofacial area of patients and controls. - Measurements: Three hundred five female patients were screened to find 44 participants fulfilling the inclusion criteria, 22 suffering from MP and 22 in a control group. Sleep quality was assessed by use of the Pittsburgh Sleep-Quality-Index (PSQI) and a validated German sleep questionnaire (SF-AR). Tooth wear was assessed and anterior temporalis muscle activity was measured at home for several nights by use of a portable electromyography (EMG) device. - Results: 22 patients (45.0 ± 13.6 years) and 22 controls (45.2 ± 9.0 years) were recruited. The PSQI sum-score was 7.5 ± 3.7 for patients and 4.4 ± 3.0 for controls (p = 0.006). The SF-AR showed that 23% of the controls and 14% of the patients were "long sleepers". The overall number of episodes in the two groups was not significantly different (4.10 ± 2.65 versus 4.57 ± 1.99 episodes per hour). However, more patients had temporalis muscle activity possibly related to SB during all four consecutive nights (p = 0.04). According to the International Classification of Sleep Disorders - Third Edition (ICSD-3) criteria, 13.6% of the controls and 71.4% of the patients (p < 0.001) showed SB. - Conclusions: Sleep-associated disturbances, including reduction of sleep quality and greater prevalence of SB and facial pain in the morning, occurred significantly more often among TMD patients. Additionally, SB fluctuated over the nights especially in controls. This should be taken into consideration when the prevalence of SB is assessed by use of EMG.
Gesehen am 07.07.2020